Perlindungan Anak dari Kekerasan Ekonomi melalui Asuransi: Analisis Peran Otoritas Jasa Keuangan dalam Meningkatkan Jaminan Hak Anak - Anisatul Latifah; Arif Sugitanata; Siti Khamidatus Sholikhah (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – This research aims to elucidate in detail how insurance can serve as a vital instrument in ensuring the rights of children and shielding them from the detrimental impacts of economic violence. Methods – The research methodology employed is a thorough literature review encompassing primary data sources from pertinent books, journals, and legal texts related to the research topic. Subsequently, the acquired data is subjected to descriptive-analytical analysis to unveil the underlying objectives of the research. Findings – The results indicate that the security provided by insurance contracts is instrumental in safeguarding the rights of children, particularly in situations where parental figures have passed away or retired from employment. While the fulfillment of children's rights may not have reached an optimal level, their financial needs can be met to a reasonable extent, thanks to the role played by insurance. Additionally, this research underscores the crucial role played by the Financial Services Authority (OJK) in upholding justice and ensuring effective protection for children who are vulnerable in the context of economic violence. The OJK is tasked not only with receiving complaints but also with resolving disputes related to insurance businesses and facilitating the settlement of insurance claim disputes in accordance with the agreements reached by the involved parties. Research implications – The theoretical implication of this research lies in its contribution to broadening our comprehension of the role of insurance in the realm of child protection. Moreover, its originality is underscored by the integration of distributive justice principles and contract theory, enriching our understanding of this dynamic interplay within the context of child protection mechanisms. Originality/value – In conclusion, this research underscores the significance of collaborative efforts among governmental bodies, financial institutions, and communities in enhancing the safeguarding of children from economic violence, utilizing insurance as a potent tool for protection.